How Does B Cell Antigen Presentation Affect Memory CD4 T Cell Differentiation and Longevity? - Welsh, Robin A.; Song, Nianbin; Sadegh-Nasseri, Scheherazade (Frontiers in Immunology, 2021)
Dendritic cells are the antigen presenting cells that process antigens effectively and prime the immune system, a characteristic that have gained them the spotlights in recent years. B cell antigen presentation, although less prominent, deserves equal attention. B cells select antigen experienced CD4 T cells to become memory and initiate an orchestrated genetic program that maintains memory CD4 T cells for life of the individual. Over years of research, we have demonstrated that low levels of antigens captured by B cells during the resolution of an infection render antigen experienced CD4 T cells into a quiescent/resting state. Our studies suggest that in the absence of antigen, the resting state associated with low-energy utilization and proliferation can help memory CD4 T cells to survive nearly throughout the lifetime of mice. In this review we would discuss the primary findings from our lab as well as others that highlight our understanding of B cell antigen presentation and the contributions of the MHC Class II accessory molecules to this outcome. We propose that the quiescence induced by the low levels of antigen presentation might be a mechanism necessary to regulate long-term survival of CD4 memory T cells and to prevent cross-reactivity to autoantigens, hence autoimmunity.